Falling in Love on Willow Creek - Mason, Debbie (Novelist); Mason, Debbie (Novelist). (New York : Forever, 2021)
In this latest Highland Falls romance, a single mom-to-be is rescued by an undercover FBI agent who makes her believe in love again.
Keywords: United States -- Federal Bureau of Investigation -- Officials and employees; Fiction; Man-woman relationships -- Fiction; Unmarried mothers -- Fiction; Undercover operations -- Fiction; Romance fiction